2020
DOI: 10.1371/journal.pone.0228046
|View full text |Cite
|
Sign up to set email alerts
|

Non-mycosis fungoides cutaneous lymphomas in a referral center in Taiwan: A retrospective case series and literature review

Abstract: Background While mycosis fungoides (MF) and Sé zary syndrome (SS) are the most common cutaneous lymphomas (CLs), there is limited data about non-MF/SS CLs. Objective We aimed to evaluate clinical characteristics of non-MF/SS CLs. Methods A retrospective analysis evaluated patients with non-MF/SS CLs covering a period of 17 years. The records of 59 patients with non-MF/SS CLs were reviewed for demographic profiles, clinical features, and survival outcomes. Results Our series consisted of 38 non-MF/SS cutaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 42 publications
2
11
1
Order By: Relevance
“…Nonetheless, ethnic and environmental factors may have influenced this disease distribution. 17,18 In harmony with previous reports, 17,18,26 about 5% of our patients had blood involvement, 17% presented with T3 and T4 skin lesions, 22% revealed significant peripheral lymph nodes and most MF patients (79.6%) were presented at an early stage (IA and B).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Nonetheless, ethnic and environmental factors may have influenced this disease distribution. 17,18 In harmony with previous reports, 17,18,26 about 5% of our patients had blood involvement, 17% presented with T3 and T4 skin lesions, 22% revealed significant peripheral lymph nodes and most MF patients (79.6%) were presented at an early stage (IA and B).…”
Section: Discussionsupporting
confidence: 90%
“…The potential utility of these markers to differentiate CTCL from its mimickers is also addressed with the secondary aim to highlight the demographic profiles, relative frequencies, common clinicopathological features and staging distribution of this relatively rare entity in our locality. Demographically, CTLC patients had a lower mean age as compared to worldwide studies, 1,[16][17][18] but matched one national study. 10 However, dermatoses patients exhibited the average mean age defined for these conditions.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Regarding extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT), several authors have indicated a higher frequency of this condition in Asian countries compared to in Western countries and a strong association between Epstein-Barr virus (EBV) and ENKTCL in Asian populations [ 33 35 ]. However, we found only 1 case (0.7%) of ENKTCL-NT in our study, which was lower than reported in other Asian countries [ 8 10 , 36 ]. In our center experience, many patients with ENKTCL-NT present with extracutaneous manifestations, this can be the explanation of a low rate of primary cutaneous ENKTCL-NT.…”
Section: Discussioncontrasting
confidence: 92%